Isotretinoin embryopathy: report of one case - Cláudia Patraquim; Albina Silva; Ângela Pereira; Miguel Gonçalves-Rocha; João Fernandes; Almerinda Pereira (Hygeia Press di Corridori Marinella, 2015)
Retinoic acid is a derivative of vitamin A. Retinoic acid embryopathy is an association of malformations caused by the teratogenic effect of retinoic acid, a drug used for the treatment of cystic acne. Isotretinoin is also known as 13-cis-retinoic acid. The risk of malformations after exposure to oral isotretinoin has been evaluated to be around 20%. Affected infants may present craniofacial, central nervous system, cardiac, and thymus abnormalities. There is also an increased risk of spontaneous abortions and premature delivery. Isotretinoin may also have effects on child behavior in about 30-60% of children exposed to it. Termination of pregnancy may be considered in cases of pregestational and/or gestational exposure to isotretinoin. The authors present the case of an infant male who was the first child of young, healthy, unrelated parents, whose mother was exposed to isotretinoin in both pregestational and gestational periods. He had a developmental delay, craniofacial abnormalities (low-set and dysplastic ears with anteverted lobules, frontal upsweep, hypertelorism, flat nasal bridge and prominent filter) and apparent articular hypermobility, more obvious in his knees. Brain magnetic resonance imaging showed absence of cerebellar vermis, midbrain dysplastic configuration with thickened superior cerebellar peduncles, decreased thickness of pons-midbrain transition, right cerebellar hemisphere dysplasia, mild decrease in corpus callosum thickness, and enlarged pericerebral subarachnoid space. The features described are compatible with isotretinoin embryopathy, according to the literature. This case aims to raise awareness about the use of teratogenic drugs in women of childbearing age, especially isotretinoin, and the importance of information regarding effective contraceptive methods, with compulsory pregnancy testing.